Author Correction: Signatures of the topological s+− superconducting order parameter in the type-II Weyl semimetal T d -MoTe2 - Z. Guguchia (Nature Portfolio, 2018)
The original version of this article omitted the following from the Acknowledgements: “CAM and AL were supported by the NSF MRSEC program through Columbia in the Center for Precision Assembly of Superstratic and Superatomic Solids (DMR-1420634). Additionally, this research used resources of the National Energy Research Scientific Computing Center, a DOE Office of Science User Facility supported by the Office of Science of the U.S. Department of Energy under ‘Contract No. DE-AC02-05CH11231’.” This has now been corrected in both the PDF and HTML versions of the article.